RASYWAH DALAM PANDANGAN RASULULLAH: TINJAUAN KESAHIHAN DAN PEMAHAMAN HADIS - Yusrizal Efendi (JURIS (Jurnal Ilmiah Syariah), 2018)
Bribe was not new affair in societies. This cruel phenomenon had became worse and worse. This bad habit happened at any societies’ life. Considering the massive damage of it, Islam forbade moslem people to do bribery, even prophet Muhammad cursed his follewers to do it. It was not forbidden to people who give something or receiver, but also to the one who mediate this bribery.